CORAK TAFHIM AL-QUR’AN DENGAN METODE MANHAJI - Ari Anshori (Universitas Muhammadiyah Surakarta, 2015)
many varieties and ways for someone to understand al-Qur’an or tafhim al-Qur’an. It is because one’s ability to understand and to explain about the essence of Allah’s commandment is different, based on his/her ability and understanding himself/herself. The difference in understanding is not separable from many factors, among other are: the level of intellegence, the level of education, the level of underlying religious understanding. The focus of problem in this research was to find the proper formulation of tafhim, in order that the messages contained in al-Qur’an are easy to understand correctly based on the text and the context of the referred verse. The results of the research were: that al-Qur’an has verses in the forms of muhkamat and mutasyabihat, therefore, to understand them, aided tools are needed such as tafhim manhaji, in order that the messages contained on them can be understood correctly based on the referred text and context. Although it is proper to appreciate if every effort of tafhim and interpretation of al-Qur’an always uses a method or strategy of new study, including a new style contained in the tafhim manhaji of al-Qur’an, because the method of tafhim manhaji is considered as being able to reduce many kinds of abstruse in understanding the verses of Allah written in al-Qur’an or verses which are broadly spread on this universe.